2017
DOI: 10.1111/resp.13114
|View full text |Cite
|
Sign up to set email alerts
|

A clinical approach to the threat of emerging influenza viruses in the Asia‐Pacific region

Abstract: Seasonal influenza epidemics and periodic pandemics are important causes of morbidity and mortality. Patients with chronic co-morbid illness, those at the extremes of age and pregnant women are at higher risks of complications requiring hospitalization, whereas young adults and obese individuals were also at increased risk during the A(H1N1) pandemic in 2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 98 publications
0
26
0
Order By: Relevance
“…It was also effective against subtypes of T-20-resistant HIV mutants and primary HIV-2 isolates. A further assay from the same group led to the improvement of 2P23 which, by adding a fatty acid group (C 16 ) to its C terminus, produced LP-19 [16]. The results showed that LP-19 could inhibit HIV-1, -2 and SIV in much lower concentrations than 2P23, especially in the assay for inhibition of virus entry.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also effective against subtypes of T-20-resistant HIV mutants and primary HIV-2 isolates. A further assay from the same group led to the improvement of 2P23 which, by adding a fatty acid group (C 16 ) to its C terminus, produced LP-19 [16]. The results showed that LP-19 could inhibit HIV-1, -2 and SIV in much lower concentrations than 2P23, especially in the assay for inhibition of virus entry.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…The influenza virus presents a major threat to human health as it has been responsible for many epidemics over the years [16]. Given their segmented single-stranded RNA genome, influenza viruses have a high degree of genomic variation, which is caused by point mutation changes or large sequence reassortment [153], triggered when an animal is infected by different strains of influenza that can exchange genome segments, thus resulting in a new strain [154].…”
Section: Influenza Virus Inspired Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the influenza A (H1N1) pandemic in 2009, seasonal influenza remains a critical public health issue (1). Besides neuraminidase inhibitor treatment, influenza pneumonia often requires hospitalization and antibiotic therapy for a possible bacterial coinfection (2).…”
Section: Introductionmentioning
confidence: 99%
“…The 2009 H1N1 pandemic virus disproportionately affected children and young adults. Patients with chronic co-morbid illness, and those at the extremes of age and pregnant women are at higher risks of complications requiring hospitalization [3]. The 2009 H1N1 pandemic virus spread was so rapid that with 168 countries reported infections by mid-2009 [4] with more than 162,000 laboratory-confirmed cases and over a thousand human deaths [5].…”
Section: Introductionmentioning
confidence: 99%